3D PCL/fish collagen composite scaffolds incorporating osteogenic abalone protein hydrolysates for bone regeneration application: in vitro and in vivo studies. Issue 3 (11th February 2021) - Oh, Gun-Woo; Nguyen, Van-Tinh; Heo, Seong-Yeong; Ko, Seok-Chun; Kim, Chang Su; Park, Won Sun; Choi, Il-Whan; Jung, Won-Kyo
Abstract: Three-dimensional (3 D) printing is an effective technology that has shown considerable potential for use in tissue regeneration. Of the many materials that have been proposed for this purpose, poly (ε-caprolactone) (PCL) 3 D scaffolds have been received significant attention in the bone tissue engineering field due to its advantageous mechanical properties and biocompatibility. In this study, a novel method was developed for tissue-engineered bone that combines PCL 3 D scaffolds with fish collagen (Col) and the osteogenic abalone intestine gastro-intestinal digests (AIGIDs) from Haliotis discus hannai . And then, mouse mesenchymal stem cells (MSCs) were seeded onto the fabricated scaffolds. After in vitro culturing, the proliferation of the MSCs on the scaffolds, alkaline phosphatase (ALP) activity, and the amount of deposited calcium were investigated. The results indicated that the ALP activity and mineralization in PCL/AIGIDs/Col was higher than that of the other scaffolds. In an in vivo experiment, the two fabricated scaffolds were implanted in a rabbit tibia. PCL/AIGIDs/Col group exhibited strong osteoinduction capability in the rabbit tibia defect model. These stimulated biological responses in vitro and in vivo suggest that the PCL/AIGIDs/Col scaffold are promising material for use in tissue implants and bone regeneration.